Aholoa Lāna'i! - May K. Kealoha (JMIR Publications, 2020)
Asthma is a major public health concern for the state of Hawai'i, where 10% of adults reported current asthma status in 2016 (Centers for Disease Control and Prevention, 2018). Each county reported high prevalence rates: Hawai'i, 19.6%; Honolulu, 17.3%; Kaua'i, 15.4%; Maui, 17.2% (Hawai'i Health Data Warehouse, 2016). Lāna'i is the smallest island in the State consisting of 141 square miles and a population of 3,102 (U.S. Census Bureau, 2018). Although robust asthma data exist for metropolitan Honolulu, statistics are unavailable for Lāna'i. If data were to be extrapolated using whole ethnic populations and adult asthma rates (Hawai'i Health Data Warehouse, 2016), 184 (13%) Filipinos and 200 (28.4%) part-Hawaiian and other Pacific Islanders may be affected by the condition.